2012
DOI: 10.1126/science.1226132
|View full text |Cite
|
Sign up to set email alerts
|

Biotinylated Rh(III) Complexes in Engineered Streptavidin for Accelerated Asymmetric C–H Activation

Abstract: Enzymes provide an exquisitely tailored chiral environment to foster high catalytic activities and selectivities, but their native structures are optimized for very specific biochemical transformations. Designing a protein to accommodate a non-native transition metal complex can broaden the scope of enzymatic transformations while raising the activity and selectivity of small molecule catalysis. Herein, we report the creation of a bifunctional artificial metalloenzyme in which a glutamic acid or aspartic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
371
0
11

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 744 publications
(394 citation statements)
references
References 37 publications
(34 reference statements)
4
371
0
11
Order By: Relevance
“…4 and Table 1). The distorted capsules provided the product in close to a 1:1 ratio, indicating that most of the cavity effect was lost (entries [8][9][10][11]. The application of ZnTPP-m,mOMe even displayed a small preference for the production of the 2-aldehyde (entry 8).…”
Section: Formation Of Capsulesmentioning
confidence: 99%
See 1 more Smart Citation
“…4 and Table 1). The distorted capsules provided the product in close to a 1:1 ratio, indicating that most of the cavity effect was lost (entries [8][9][10][11]. The application of ZnTPP-m,mOMe even displayed a small preference for the production of the 2-aldehyde (entry 8).…”
Section: Formation Of Capsulesmentioning
confidence: 99%
“…As a consequence, tailoring enzymes for synthetic applications also involves modifications of the enzyme cavity, rather than the active site. The catalytic performance of enzymes is nowadays routinely modified by using directed evolution and site-mutagenesis 7 , and also for artificial metallo-enzymes this has been demonstrated to be powerful 8,9 . These working principles have also inspired chemists for decades and enzyme mimics have been prepared and studied [10][11][12][13][14] to understand them, and also to increase the tool box of methods for performing chemical transformations efficiently.…”
mentioning
confidence: 99%
“…27 Importantly, the use of aminoacyloxy internal oxidants allows mild reaction conditions and therefore the possibility of using alkenes as partners, 25b something that had been elusive in other annulation reactions involving these type of C-H activation protocols owing to the competence of β-hydride elimination processes.The annulation can also be accomplished in an asymmetric manner, as recently shown by the groups of Cramer, 28 and of Rovis and Ward (Scheme 16). 29 Cramer and coworkers developed a chiral Cp ligand with C2-symmety whereas the Rovis and Ward collaborative publication describes an elegant synthesis of a biotinylated-Cp ligand for Rh(III) that upon interacting with a biotine binding protein generates a chiral environment that is transduced in the formation of enantiomerically rich products. In addition to benzamides, it has been shown that other related susbtrates like acrylamides, sulfonamides, or sulfoximides, can also be engaged in mechanistically related metal-catalyzed annulations.…”
Section: (4+2) Annulationsmentioning
confidence: 99%
“…stereoselectivity. [6,20,21] Alternatively, streptavidin has been equipped with transporters such as cellpenetrating poly(disulfide)s (CPDs). [4,22] The resulting primary systems 10 turned out to enter cells as easily as expected.…”
Section: Te Rtiary Systemmentioning
confidence: 99%